HIPEC after Interval Debulking Surgery as Best Clinical Practice in Ovarian Cancer Patients: Case Series and Literature Review - Stefano Restaino; Jessica Mauro; Stefano Cianci; Alessandro Buda; Claudia Andreetta; Elena Poletto; Enrico Maria Pasqual; Alice Poli; Cosimo Vittorio Agrimi; Doriana Armenise; Alice Buzzelli; Domenico Caccamo; et al. (IMR Press, 2022)
Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) combined with interval debulking surgery (IDS) constitutes an adjunctive treatment strategy in advanced ovarian cancer (AOC). This approach is based on the concept of perfusing chemotherapy targeting directly the site of residual tumor after optimal surgical debulking. It improves patients' outcome in terms of overall survival (OS) and disease free survival (DFS). The correct selection of patients eligible for IDS + HIPEC is crucial: in particular, they must have shown a good response to neoadjuvant chemotherapy (NACT) and have a good performance status (PS). The application of HIPEC at the end of debulking does not seem to increase neither the rate of intra/postoperative complications nor the time of hospitalization. Clinical Cases: After approving an internal protocol for the application of HIPEC in our hospital, we have submitted four patients to IDS + HIPEC in the past 12 months. One of these patients underwent a minimally invasive procedure. No intra- or postoperative complications were observed. Results: All patients underwent IDS + HIPEC after being assessed as eligible and after showing a good response to NACT. In the course of IDS in all cases complete debulking was achieved. No patient developed intra- or postoperative complications. Conclusions: The addition of HIPEC to interval debulking surgery should be offered to all eligible patients, considering that the association of HIPEC to IDS seems to improve patients' outcomes in terms of OS and DFS, without increasing post-operative morbidity .